Errors Made by English Literature Students in Translating News Text - Mochamad Rizqi Adhi Pratama; Maya Kurnia Dewi (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
The research is aimed at describing the types of translation errors made by the English Literature Students in translating news text from English into Indonesian. The present study employed a descriptive qualitative study. The research subject was the sixth-semester students of the English Literature Study Program, Faculty of Economics, Law, and Humanities, Universitas Ngudi Waluyo who have taken a Translation Course. The news text was taken from the Jakarta Post and it consists of 22 paragraphs. The news texts were then translated into Bahasa Indonesia and they become the target texts as the sources of data to investigate the students’ translation errors. They were then classified into five types of errors according to Vilar et al. (2006, 698). The research results revealed that there were 108 translation errors in the form of incorrect words (60,2%), punctuation (18.5%), missing words (12,03%), and word order (0,9%). It can be concluded that the most frequent errors made by the students are incorrect words, punctuation, and missing words.